DRM and Modchips: Time for the Court of Justice to do the “Right” Thing - Gillen, Martina (SCRIPT-ed, 2014)
This paper looks at three key cases; UsedSoft (C-458/13), PC Box (C-355/12) and Grund (C-458/13), on the topic of the extent and nature of a copyright holders ability to constrain future uses of their copyrighted works in the field of software and critically considers the interaction between copyright and competition law in these judgements. In UsedSoft, the Court of Justice of the European Union (hereafter CJEU) shook the common-law world by suggesting that under certain circumstances the licensing of a piece of software could constitute a sale, they achieved this by focusing on the balance of right between the user and the vendor and more importantly, on the “specific subject matter” of the right granted. In PC Box, a more economically cautious judgement, but one with intellectual consonance with UsedSoft, the CJEU looked at the issue of 'modchips' to permit homebrew and other non-approved games to be played on Nintendo consoles. They decided that the TPM (technological protection measures) embedded in the consoles were analogous to the other more traditional methods of encryption and DRM (digital rights management) employed in standard software. However, the judgement also highlighted that the use of a balancing test with regard to the appropriateness of the TPM devices in consoles was necessary. Furthermore, the Court judged that the national courts should carry out a 'real world' market test to see if the use of modchips truly adversely affected the interests of the copyright holder i.e. how of then they were used for infringing as opposed to non-infringing uses. Finally, we shall consider the key case that never was - Grund. This case was, and remains, something of an enigma as the preliminary reference questions were difficult to comprehend but nevertheless promised important clarifications in the law. However, we will consider it in this discussion largely because the reference was ultimately withdrawn because the parties were convinced that the issue was resolved by the judgement in PC Box. Thus it offers an insight into the future utility of the UsedSoft and PC Box judgements.